Analysis Of Changes In Endothelin-1 (Et-1) And F2-Isoprostane Levels After The 30 Km Event In The Makassar Bike Community At The "Bike For Health" Event - Nur Fadhilah Irfani; Ilhamjaya Pattelongi; Andi Ariyandy; Andi Wardihan Sinrang; Djohan Aras; Nukhrawi Nawir (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2023)
This study aims to determine changes in ET-1 and F2-isoprostane levels after a 30 km cycling event in the Makassar cycling community. This study used a pre-experimental with one group pretest-posttest design on 30 male cyclists aged 30-60 years. The sampling technique used is the purposive sampling method. The pretest was carried out the day before the 30 km cycling event, then the post-test was carried out 2 hours after the cycling event. Blood testing is done with an ELISA Kit. Data were analyzed using the Wilcoxon test to see changes in ET-1 and F2-isoprostane levels after cycling events. The correlation of changes in ET-1 and F2-isoprostane levels was analyzed using the Spearman test. The results of this study found that the 30 km cycling event had no significant effect on changes in levels of ET-1 (p=0.082) and F2-isoprostane, which means that it has no potential to increase the body's oxidative stress (p=0.688). Changes in ET-1 levels did not correlate with changes in F2-isoprostane levels which showed no association with impaired cardiovascular function (p=0.102).